PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL MATERI KOREKSI ALIS PADA MATA PELAJARAN DASAR KECANTIKAN SISWA KELAS X SMK PARIWISATA IMELDA MEDAN - Puspita, Tiara Dinda; Febiola Angel Kusuma Wati; Farihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was prompted by pedagogical difficulties encountered by class X Beauty Therapy students at SMK Pariwisata Imelda Medan who struggled to master eyebrow correction techniques. The core problems stemmed from the students' inability to structure eyebrows with precision and symmetry according to specific facial types, combined with a lack of interactive learning media that limited self-directed study due to dependence on traditional textbooks. The objectives of this study were to design a digital electronic module (e-modul) for eyebrow correction, evaluate its instructional feasibility through expert verification. The methodology utilized was Research and Development (R&D) incorporating the structured ADDIE framework (Analyze, Design, Develop, Implement, Evaluate). The participants involved consisted of 3 subject experts, 3 media specialists, and 30 beauty vocational students. Non-test protocols, including initial needs questionnaires and evaluation forms, were utilized to collect data, which were processed through quantitative descriptive statistical percentage analysis. The feasibility assessments illustrated remarkable product quality. Evaluations by subject matter experts delivered a suitability rating of 90%, whereas media designers scored the architecture at 91%. The cumulative expert validation reached an average of 90%, qualifying the tool under the "Excellent" category. Concurrently, user field implementations reflected outstanding reception. Feedback from the small-scale trial recorded 87%, the medium-scale trial documented 91%, and the large-scale trial peaked at 92%, securing an overall satisfaction average of 90% ("Excellent"). Thus, the developed eyebrow correction module is declared suitsble and effective to be used as a learning medium for students of class X SMK Tourism Imelda Medan.